Tabaquismo y su influencia en la enfermedad pulmonar obstructiva crónica (EPOC) en adultos de 40 a 70 años del sector voluntad de dios 1 del cantón Babahoyo, Los Ríos periodo septiembre 2017 a febrero 2018 - Ramos Tapia, Jazmin Lizbeth (2018)
Chronic obstructive pulmonary disease, known as COPD, is a complex and heterogeneous disease, with a high incidence and high mortality, but preventable and treatable. It is characterized by the limitation of airflow due to the inflammatory response of the lungs to harmful particles, such as those produced by tobacco, this is the most important cause of the disease, so the research aims to improve the quality of life of the inhabitants of the Voluntad de Dios Sector 1. The research project whose problem was: How does smoking influence the development of COPD in adults aged 40 to 70 years in the sector of the will of God 1 of the Babahoyo canton ?, allowed for an observational, descriptive and cross-sectional epidemiological study on the epidemiological characteristics of the people who smoke and those who suffer from COPD through the analysis of the information collected, it was possible to determine in the graphic representation that 68% of the population is unaware of the diseases that cause daily tobacco consumption, which is why some smoke without taking into account the effects they cause for their health, 85% of the inhabitants of the Voluntad de Dios sector 1, present respiratory symptoms due to the atmospheric environment due to contamination in the smog environment, and 93% present respiratory symptoms, 39% of the population have respiratory tract infections and 31% have obstructive pulmonary disease chronic, so it is considered feasible to provide the population with educational talks in their community about tobacco and its possible consequences on their health, which are related to COPD, in some cases it is known that it is impossible to rely only on talks and prevention because tobacco has gained more influence in recent times, so this research seeks to reduce mortality rates in the city of Babahoyo.